Scaffolding theory of maturation, cognition, motor performance, and motor skill acquisition: a revised and comprehensive framework for understanding motor–cognitive interactions across the lifespan - Klotzbier, Thomas Jürgen; Schott, Nadja (Frontiers in Human Neuroscience, 2025)
The Scaffolding Theory of Maturation, Cognition, Motor Performance, and Motor Skill Acquisition (SMART COMPASS) provides a revised, integrative framework for understanding the dynamic relationship between motor and cognitive systems across the lifespan. Integrating concepts from the Scaffolding Theory of Aging, the Integrated Framework for Cognitive and Motor Skill Development, and the OPTIMAL Theory of Motor Learning, the model demonstrates how neural, environmental, and behavioral factors jointly shape cognitive and motor performance. Its unique contribution lies in bridging neurobiological mechanisms (e.g., neuroplasticity and cognitive reserve), psychological drivers (e.g., autonomy and self-efficacy), and motor learning principles into a unified, lifespan-oriented approach. Unlike existing frameworks, SMART COMPASS explicitly links structured physical training and motor skill learning to long-term brain adaptability. The model is based on three core pillars: (1) Nature and Nurture, emphasizing the interaction between genetic predispositions and environmental influences; (2) Structural-Functional Neurocognition, focusing on neuroplasticity, brain reserve, and compensatory scaffolding; and (3) Motor Behavior, which explores the role of executive functions, representations, and autonomy in skill acquisition and learning efficiency. A key aspect of SMART COMPASS is emphasizing physical fitness and autonomy-supportive environments to promote cognitive-motor performance. For example, in aging populations, SMART COMPASS can guide tailored interventions combining cardiovascular training with task-specific motor learning to maintain executive function and reduce fall risk. Similarly, structured motor programs supporting autonomy and self-efficacy can enhance motor competence and academic performance in child development. It highlights how exercise, self-efficacy, and autonomy-supportive environments can enhance neuroplasticity and learning potential, providing practical insights for motor skill development, rehabilitation, and lifelong cognitive-motor optimization interventions.